A critical review of Antarctic Conoidea (Neogastropoda). (2nd July 2016) - Kantor, Yuri I.; Harasewych, Myroslaw G.; Puillandre, Nicolas
ABSTRACT: The Antarctic Conoidean fauna is critically reviewed based on published data and specimens in the collections of the USNM, IORAS and MNHN. Forty-two species and subspecies of the superfamily Conoidea are recorded as occurring within the Antarctic Convergence (excluding the fauna of the Kerguelen Islands) and are attributed to 14 genera and seven families. These include the new taxa: Antarctospira n. gen. (type species— Leucosyrinx badenpowelli Dell, 1990); Drilliola antarctica n. sp.; Pleurotomella ( Pleutoromella ) tippetti n. sp.; Pleurotomella ( Anomalotomella ) petiti n. sp.; Xanthodaphne pastorinoi n. sp. Aforia watsoni is introduced as a new name for Pleurotoma ( Surcula ) lepta Watson, 1881, non Pleurotoma lepta Edwards, 1861. A lectotype is designated for Conorbella antarctica (Strebel, 1908). New combinations are also proposed. Antarctospira badenpowelli (Dell, 1990), n. comb. (previously assigned to Leucosyrinx ); Antarctospira principalis (Thiele, 1912), n. comb. (previously assigned to Typhlomangelia ); Antarctospira mawsoni (Powell, 1958), n. comb. (previously assigned to Leucosyrinx ); Typhlodaphne paratenoceras (Powell, 1951), n. comb. (previously assigned to Leucosyrinx ); Belalora weirichi (Engl, 2008), n. comb. (previously assigned to Oenopota ); Pleurotomella ( Anomalotomella ) innocentia (Dell, 1990), n. comb. (previously assigned to Typhlodaphne ); Pleurotomella ( Anomalotomella ) nipri (Numanami, 1996), n. comb. (previously assigned to Typhlodaphne ); Xanthodaphne raineri (Engl, 2008), n. comb. (previously assigned to Pleurotomella ); Aforia hedleyi (Dell, 1990), n. comb. (previously assigned to Pontiothauma ). The majority of Antarctic conoidean taxa have hypodermic marginal teeth. Although there is a similar relative abundance of conoideans in Antarctic waters to that seen in other well-studied faunas, the low number of conoideans is indicative of the general impoverishment of the gastropod fauna in the region. Fourteen percent (2 of 14) of conoidean genera that occur within the Antarctic Convergence are endemic to Antarctic waters, as are 82% (34 of 42) of the species. Most taxa have very broad bathymetric ranges, some extending from bathyal to hadal depths. The greatest species diversity was at bathyal depths.